2007
DOI: 10.1002/ajmg.b.30471
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of candidate genes for DYX1 and DYX2 in families with dyslexia

Abstract: Dyslexia is a common heterogeneous disorder with a significant genetic component. Multiple studies have replicated the evidence for linkage between variously defined phenotypes of dyslexia and chromosomal regions on 15q21 (DYX1) and 6p22.2 (DYX2). Based on association studies and the possibility for functional significance of several polymorphisms, candidate genes responsible for the observed linkage signal have been proposed-DYX1C1 for 15q21, and KIAA0319 and DCDC2 for 6p22.2. We investigated the evidence for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
86
3
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 80 publications
(104 citation statements)
references
References 31 publications
5
86
3
1
Order By: Relevance
“…The results did not support association for the two SNPs reported as associated with dyslexia in Finnish readers. 1 These findings are consistent both with other data, suggesting that the association of markers rs3743205 and rs61761345 identified by Taipale et al may be specific to the Finnish genetic background 4 and with other data suggesting that DYX1C1 is nevertheless associated with reading disability in non-Finnish populations, 28,31 as well as with short-term memory. 28,30 Overall, these data significantly increase support for a role of DYX1C1 in dyslexia and, perhaps separately, in short-term storage of verbal information.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The results did not support association for the two SNPs reported as associated with dyslexia in Finnish readers. 1 These findings are consistent both with other data, suggesting that the association of markers rs3743205 and rs61761345 identified by Taipale et al may be specific to the Finnish genetic background 4 and with other data suggesting that DYX1C1 is nevertheless associated with reading disability in non-Finnish populations, 28,31 as well as with short-term memory. 28,30 Overall, these data significantly increase support for a role of DYX1C1 in dyslexia and, perhaps separately, in short-term storage of verbal information.…”
Section: Discussionsupporting
confidence: 90%
“…29 The effect was mostly accounted for by an association with short-term memory, supporting the finding of Marino et al 30 that the SNPs reported by Taipale may be related more to short-term memory than to dyslexia. Brkanac et al 31 recently reported a nominally significant association of rs61761345 in a sample of 191 dyslexic probands, together with their parental and matched unrelated controls.…”
Section: Introductionmentioning
confidence: 99%
“…The most common test that was used to assess intelligence was the Wechsler Intelligence Scale for Children. Five of the samples also reported the use of neurological, medical or sensorial disorders as exclusionary criteria, although the specific disorders that were screened varied across the samples [Bellini et al, 2005;Brkanac et al, 2007;Marino et al, 2007;Newbury et al, 2011] (Toronto sample, this study).…”
Section: Tran Et Al 151mentioning
confidence: 99%
“…In a family-based association study by Wigg et al [2004], a different marker rs11629841 was found to be significantly associated with RD which was in high LD with both À3G/A and 1249G/T. Brkanac et al [2007] found association with the 1249G/T polymorphism, but it was the major G allele that was overtransmitted, rather than the T allele which showed association in the study by Taipale et al [2003]. A number of other studies did not find association between DYX1C1 SNPs and RD [Bellini et al, 2005;Cope et al, 2005;Marino et al, 2005;Saviour et al, 2008;Newbury et al, 2011;Venkatesh et al, 2011].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation